Developing learning in early childhood - Bruce, Tina. (London : P. Chapman Pub. ; Thousand Oaks, Calif. : Sage Publications, 2004)
Shows how adults can support children and actively help them develop their learning in early childhood. Drawing on traditional approaches as well as recent research and theories.
Includes bibliographical references and index.
Keywords: Early childhood education -- Parent participation; y